Tanggung Jawab Afi Tour Travel Haji dan Umrah pada Penundaan Keberangkatan Jamaah dalam Persepktif Hukum Ekonomi Syariah - Viera Inesya Puteri; Hana Pertiwi (CV. Doki Course and Training, 2025)
The implementation of the Hajj and Umrah pilgrimages, causing delays and cancellations which have given rise to legal and economic problems. The main point of this research is the form of responsibility of AFI Tour Travel towards delayed Hajj pilgrims and how sharia economic law reviews the responsibilities of AFI Tour Travel towards delayed Hajj pilgrims. The purpose of this research is to determine the form of responsibility of AFI Tour travel towards delayed Hajj pilgrims and to find out a review of sharia economic law regarding the responsibility of AFI Tour travel towards delayed Hajj pilgrims. There were 6 respondents to this research, namely 2 AFI Tour Travel travel administrators and 4 pilgrims who were delayed. The research method used is empirical juridical research, namely research that combines law with observational data analysis by means of field observation, direct interviews with respondents, and documentation. Data analysis in this research is qualitative analysis. The results of this research are that AFI Tour Travel's responsibility for Hajj pilgrims who are delayed due to Covid is included in force majeure or default. The responsibilities given are to negotiate with the congregation and reschedule departures to a time that allows as well as providing communication and transparency to the congregation. In reviewing sharia economic law regarding AFI Tour's responsibility towards pilgrims who are delayed due to Covid, it is correct and appropriate because through deliberation they made a new contract and fulfilled the contents of the contract.